2022
DOI: 10.1088/1742-6596/2176/1/012057
|View full text |Cite
|
Sign up to set email alerts
|

Experimental seeders for sowing unseeded seeds

Abstract: Information on the use of seeders for sowing seeds of agricultural crops and their converted experimental seeders for sowing unseeded seeds is given in this article. It has been shown that such sowing units do not fully meet the agro technical requirements for sowing unseeded seeds. Most of the research focused on the issues of unloading seeds from the bunker, but did not study the laws of their movement inside the bunker. The authors have proposed a separate two-section hopper for the seeding row of the seede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The pre-Jurassic complex of the Ustyurt region is still poorly studied and probably contains a high potential for oil and gas (by analogy with sections of adjacent territories of the Caspian Sea, etc. ), the effectiveness of which is largely determined by the degree of its study [21,22]. The volume of core material obtained over the last period contributed to the filling of a number of "white spots" in the geological structure of the Pre-Jurassic section of the studied area and adjacent zones [5].…”
Section: Resultsmentioning
confidence: 99%
“…The pre-Jurassic complex of the Ustyurt region is still poorly studied and probably contains a high potential for oil and gas (by analogy with sections of adjacent territories of the Caspian Sea, etc. ), the effectiveness of which is largely determined by the degree of its study [21,22]. The volume of core material obtained over the last period contributed to the filling of a number of "white spots" in the geological structure of the Pre-Jurassic section of the studied area and adjacent zones [5].…”
Section: Resultsmentioning
confidence: 99%
“…In the studies carried out in the open pit, leaching processes were observed in 68% of the bed. It was found that the total length of the open B-13-2 ditch was 4260 m, and it serves to divert underground seepage water from the area of 565 ha and water from the incoming ditches away from the cultivated fields [13,14,15]. Besides, the average slope was i=0.00215.…”
Section: Resultsmentioning
confidence: 99%